Localized surface plasmons in structures with linear Au nanoantennas on a SiO2/Si surface - Milekhin, Ilya A.; Kuznetsov, Sergei A.; Rodyakina, Ekaterina E.; Milekhin, Alexander G.; Latyshev, Alexander V.; Zahn, Dietrich R. T. (Beilstein Journal of Nanotechnology, 2016)
The study of infrared absorption by linear gold nanoantennas fabricated on a Si surface with underlying SiO2 layers of various thicknesses allowed the penetration depth of localized surface plasmons into SiO2 to be determined. The value of the penetration depth derived experimentally (20 ± 10 nm) corresponds to that obtained from electromagnetic simulations (12.9–30.0 nm). Coupling between plasmonic excitations of gold nanoantennas and optical phonons in SiO2 leads to the appearance of new plasmon–phonon modes observed in the infrared transmission spectra the frequencies of which are well predicted by the simulations.
Keywords: nanoantenna array; localised surface plasmon resonance; plasmon–phonon interaction; phonons; SiO2